RGD-Conjugated Resveratrol HSA Nanoparticles as a Novel Delivery System in Ovarian Cancer Therapy - Long Q; Zhu W; Guo L; Pu L (Dove Medical Press, 2020)
Qifang Long, Weipei Zhu, Liangsheng Guo, Li Pu Department of Gynecology and Obstetrics, The Second Affiliated Hospital of Soochow University, Suzhou, People’s Republic of ChinaCorrespondence: Weipei Zhu Email weipeizhu@163.comBackground: To establish a novel delivery system of RGD-conjugated resveratrol human serum albumin (HAS) nanoparticles in ovarian cancer therapy.Methods: The nanoparticles system was characterized for physicochemical properties, the stability in the serum and in vitro release. The comparison between RVT injection, HSA-RVT NPs and RGD-HSA-RVT NPs regarding tissue distributions and pharmacokinetics was also carried out using mice as the animal models.Results: The results showed that RGD-HSA-RVT NPs were characterized of small particle size about 128.2 nm and negative zeta potential about − 21.42 mV, and drug controlled to release slowly on a biphasic pattern. Compared with control groups, RGD-HSA-RVT NPs showed the higher cellular uptake and cell inhibition rates. In vivo data showed that RGD-HSA-RVT NPs have good tumor enrichment characteristics and a significant difference in tumor inhibition, compared with the control group.Conclusion: RGD-conjugated resveratrol HSA nanoparticles are an ideal drug delivery system, which can play a role in the treatment of ovarian cancer.Keywords: resveratrol, HAS, nanoparticle, cellular uptake, cell viability, tissue distributions, pharmacokinetics